Broken drug markets in infectious diseases: Opportunities outside the private sector? - Jonathan D Alpern; Stephen J Dunlop; William M Stauffer (Public Library of Science (PLoS), 2019)
A subset of anti-infective drugs are increasingly unavailable for patients in the United States due to pricing or withdrawal from the market. Timely market solutions are needed. We assert that solutions to ensure access to some essential anti-infective agents lie outside capital markets and that public-private partnerships may be the most viable solution.